Etyka w pracy przedstawiciela medycznego - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2009)
Over the last few years, the pharmaceutical industry intensified marketing activity in Poland. One of the most important ways of promotion are visits by pharmaceutical sales representatives in physicians’ offices. Representatives during those meetings are using different sorts of tactics to manipulate physicians such as: gift-giving, free meals, travel subsidies, “fake” research, ‘white Saturdays’, sponsored teaching and conferences. An ethical ambiguity can be easily find in this work. The paper describes briefly the results of the research concerning the influence of the relationship between physicians with the pharmaceutical companies on prescribing habits which were conducted in other countries. The article presents law regulations and ethical codes present in Poland, but it concentrate on describing the results of 31 in-depth interviews with pharmaceutical sales representatives conducted between the June – November 2007. The main aim of this paper is to show how important are ethical and law standards for the pharmaceutical sales representative. Do they know it? Does companies take care about proper training and information in the area for their employees? Work ethics of the pharmaceutical sales representative is very important, and should be discussed. Drugs are special kind of goods which can influence people health and sometimes even lives so we should pay attention to the ways medicaments are advertise and promote.